Penyusunan Sistem Perencanaan Karier Pemerintah Kabupaten Klaten, Jawa Tengah - Atik Septi Winars; Ratminto Ratminto (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2011)
In any organization, institution or any institution would be expected an increase in career path for each employee or employees who are on it. Career development and promotion is not based on competence and performance but rather on the DUK (Listings Sort ranks) and even sometimes based on nepotism. Career civil servants who do not clear their determination is not supported and other factors that deserve consideration in determining an employee's career, the PNS will automatically move up and studied them on a regular basis every two years and received regular salary increases. Data collection methods used in this study were: 1) Observations and interviews conducted in each of the personnel involved in the activities of Employee Career Planning System, 2) Study of literature intended to get a design plan based on the theory that there is a career in Human Resource Management; 3) Focus Group Discussion (FGD). The results obtained in this study that the civil servant career planning system that fits the context and needs of Klaten is oriented on the competence of employees. Career planning system was developed under the provisions of current legislation.